2014
DOI: 10.3892/ol.2014.2145
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of carcinosarcoma of the renal pelvis: A case report

Abstract: Carcinosarcoma is a rare type of renal pelvis malignancy, the diagnosis of which requires the presence of malignant epithelial and mesenchymal components. The prognosis of this disease is extremely poor due to its rapid progression and widespread metastases. The present study describes a case of carcinosarcoma involving the right renal pelvis in a 73-year-old female who presented with intermittent hematuria and right-flank pain that had persisted for one month. Computed tomography revealed a 2.4×2.5 cm mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…CSRP tends to be bulky, invasive, and fast-growing [12]. It is a high-grade tumor, has a poor prognosis, and has a low survival rate [1,8]. In a study published by Wang et al, most of the patients presented with a high histological grade and advanced-stage disease [10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CSRP tends to be bulky, invasive, and fast-growing [12]. It is a high-grade tumor, has a poor prognosis, and has a low survival rate [1,8]. In a study published by Wang et al, most of the patients presented with a high histological grade and advanced-stage disease [10].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported the median cancer-specific survival time of CSRP as six months [10]. Dong et al reported the median cancer-specific survival time as one year [1]. The longest survival time in the literature was reported as two years by Chen et al [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations